A Review on Pleural Biopsy for Evaluation of Malignant Pleural Effusion - Babu, Reshma S.; Jadhav, Ulhas; Wagh, Pankaj (Challenges and Advances in Pharmaceutical Research Vol. 3, 2022)
Malignant pleural effusion (MPE) is a common symptom of a variety of cancers, including lung, breast, and lymphoma. It is critical to make an etiological diagnosis of MPE cases as soon as possible because treatment is dependent on the aetiology. The simplest and most sensitive method for detecting malignant pleural effusion is a cytopathological analysis of the fluid for malignant cells (MPE). Despite the fact that cytology is a sensitive test, many patients go undetected, necessitating a pleural histological study. Closed pleura biopsy (CPB) or thoracoscopy were advised as invasive methods. CPB was earlier considered an investigation of choice in cases of undiagnosed pleural effusion with good efficacy Since the emergence of medical thoracoscopy (MT), the use of CPB in the diagnosis of cytology negative MPE is gradually declining. Thoracoscopy, on the other hand, is rarely employed in a limited number of instances due to its high cost and difficulties. In determining MPE, CPB is less reliable than cytopathological examination of fluid or MT. Despite this, it is a simple treatment with little procedural complications. The goal of this paper is to examine the clinical presentation and treatment of MPE, as well as the role of CPB in diagnosing MPE and the benefits and drawbacks of CPB.